A proposed marketing plan for Empori Anxo Medicare Ltd. - Khan, Md. Shafiqur Rahman (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.